2021
DOI: 10.1134/s1070363221060013
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Malononitrile Dimer with Isothiocyanates

Abstract: The reaction of 2-amino-1,1,3-tricyanopropene (malononitrile dimer) with isothiocyanates leads to 1-substituted 4,6-diamino-2-thioxo-1,2-dihydropyridine-3,5-dicarbonitriles or 4,6-diamino-2-(phenylimino)-2H-thiopyran-3,5-dicarbonitrile, depending on the conditions. Quantum-chemical modeling of the IR spectra and reaction routes for the synthesized compounds was carried out. In silico predictive analysis of potential protein targets, compliance with bioavailability criteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Also, Abdel‐Latif et al (2007) reported reaction of dimer 3 with phenyl isothiocyanate in pyridine to give substituted pyrimidine. In 2021, Dotsenko et al (2021) demonstrated the reaction of malononitrile dimer 3 with isothiocyanates to give 4,6‐diamino‐2‐thioxo‐1,2‐dihydropyridine‐3,5‐dicarbonitrile derivatives or 4,6‐diamino‐2‐(phenylimino)‐2H‐thiopyran‐3,5‐dicarbonitrile, according to the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Abdel‐Latif et al (2007) reported reaction of dimer 3 with phenyl isothiocyanate in pyridine to give substituted pyrimidine. In 2021, Dotsenko et al (2021) demonstrated the reaction of malononitrile dimer 3 with isothiocyanates to give 4,6‐diamino‐2‐thioxo‐1,2‐dihydropyridine‐3,5‐dicarbonitrile derivatives or 4,6‐diamino‐2‐(phenylimino)‐2H‐thiopyran‐3,5‐dicarbonitrile, according to the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Continuing our research in the field of malononitrile dimer chemistry [24][25][26][27][28], we obtained new functional 2-(dicyanomethyl)pyridine derivatives and studied their properties. It has been previously shown that 2-cyanothioacrylamides can react with malononitrile dimer in the presence of bases to eliminate hydrogen sulfide and form dicyanomethanides 5 (Ar = 2-IC 6 H 4 ) and 7 (Scheme 2) [13,17].…”
Section: Doi: 101134/s1070363222050061mentioning
confidence: 99%
“…Due to the low solubility of the compound in DMSO-d 6 an informative 13 С DEPTQ NMR spectrum could not be registered. Mass spectrum, m/z (I rel , %): 488 (12) [M -EtO] + , 487 (28) ) was obtained on a Bruker APEX-II CCD diffractometer at 296.15 K. The structure was solved by a direct method using the Olex2 [57] and ShelXD [58] software package and refined using the SHELXL package [59]. The structure was refined by full-matrix least squares in the anisotropic approximation for non-hydrogen atoms by F 2 .…”
Section: -Phenyl-2-({[phenyl(ethoxymethyl)amino]-methyl}amino)-9-(2-c...mentioning
confidence: 99%
“…Malononitrile dimer (2-aminoprop-1-ene-1,1,3-tricarbonitrile, 10) is a reactive multifunctional reactant widely used in organic synthesis (see reviews [24,25]). Continuing studies in the field of heterocyclization reactions of malononitrile dimer [26][27][28][29][30][31][32], herein we studied the reaction of arylmethylidene derivatives of malononitrile dimer 11 with cyanoacetohydrazide 1. Compounds 11 are successfully used in organic synthesis to obtain a wide range of heterocyclic products such as furo [3,2-c]isothiazole and isoselenazole [33,34], 3-azabicyclo[3.1.0]hexane [35], 2-bromonicotinonitrile derivatives [36], new merocyanine dyes with an isoindole fragment [37], pyrido [2,3-d]pyrimidines [38], etc.…”
Section: Doi: 101134/s1070363221110025mentioning
confidence: 99%